1989
DOI: 10.1123/tsp.3.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Examining Social Support Networks among Athletes: Description and Relationship to Stress

Abstract: The purpose of this investigation was twofold: first, to describe the social support networks of athletes with respect to who provides what types of support and in what perceived amounts, and second, to compare the support networks of low- and high-stressed athletes. Results indicated that social support is provided by coaches, teammates, friends, and parents, and that each makes a unique contribution to the athletes’ social support network. Coaches and teammates were identified as providing types of support r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
53
1
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 19 publications
4
53
1
2
Order By: Relevance
“…Such support was claimed by the experts to be present mostly on field (i.e., during games or practices) and in the locker room (e.g., pre and post-performance, and during breaks). Rosenfeld, Richman, and Hardy (1989) found that 11% and 4% of collegiate athletes' emotional support came from teammates and coaches respectively. Indeed, emotional support offered by coaches, and especially by teammates, emerged as a matter of great importance for team functioning by our experts.…”
Section: Team Chemistry Through Affective Lensesmentioning
confidence: 99%
“…Such support was claimed by the experts to be present mostly on field (i.e., during games or practices) and in the locker room (e.g., pre and post-performance, and during breaks). Rosenfeld, Richman, and Hardy (1989) found that 11% and 4% of collegiate athletes' emotional support came from teammates and coaches respectively. Indeed, emotional support offered by coaches, and especially by teammates, emerged as a matter of great importance for team functioning by our experts.…”
Section: Team Chemistry Through Affective Lensesmentioning
confidence: 99%
“…The importance of coach competency complements research which has demonstrated that coaches' experience, reputations, and qualifications are important factors that influence athletes' judgments about them (Manley et al, 2008), and that provider knowledge and expertise are key factors in influencing perceptions of support (Gottlieb, 2000;Rosenfeld et al, 1989). Our results also build on ANTECEDENTS OF PERCEIVED COACH SUPPORT 20 previous work in social psychology that has noted the importance of social identity in influencing judgments of support (Haslam et al, 2004; Haslam et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This relationship appears robust regardless of whether providers and perceivers are long-standing dyads (Lakey et al, 2002) Coaches' experience, reputations, and qualifications are among the most important factors that athletes consider when making judgments about them (Manley, Greenlees, Thelwell, Filby, & Smith, 2008), and coach competency plays an important role in the development of coach-athlete relationships (Horn, 2002; Thelwell, Weston, Greenlees, Page, & Manley, 2010). Similarly, the knowledge and expertise of support providers underpins the effectiveness of support (Gottlieb, 2000;Rosenfeld et al, 1989). As such, the competency of a coach may be a key concept from which athletes form perceptions of coach supportiveness, with highly competent coaches being viewed as well qualified to provide support if it is required.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A counterargument would be to note that a less speciWc measure of social support provides a more generalizable result (Gauvin and Russell, 1993). Rosenfeld et al (1989) examined the diVerential provision of support from coaches, teammates, friends and parents. However, validation of the Social Support Survey (Richman et al, 1993) does not reveal whether all eight dimensions of support can be clearly separated.…”
Section: Discussionmentioning
confidence: 99%